Implementasi Artificial Intelligence dalam Proses Rekrutmen dan Seleksi : Studi Kasus pada PT Saripetejo Sukabumi - Wahidin, Didin; Rosmaladewi, Okke; Janaenah (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This research explores the implementation of Artificial Intelligence (AI) in recruitment and selection processes at PT Saripetejo Sukabumi. Utilizing a qualitative approach with a case study method, the study aims to analyze digital transformation in human resource management. The research focuses on identifying the AI system architecture, organizational implications, and implementation challenges. Data collection was conducted through in-depth interviews, participatory observation, and document analysis. Research findings reveal that the AI system comprises four key components: candidate filtering algorithms, machine learning-based competency analysis, automatic psychometric assessment, and intelligent virtual interview platform. AI implementation increases recruitment process efficiency by up to 60% with a candidate matching accuracy of 75%. The study uncovers that successful AI integration requires a holistic approach considering technological, ethical, and human resource development aspects. The findings provide theoretical and practical contributions to understanding digital transformation in contemporary recruitment practices